Comparing Visual Acuity, Low Contrast Acuity and Refractive Error After Implantation of a Low Cylinder Power Toric Intraocular Lens or a Non-Toric Intraocular Lens - Gundersen KG (Dove Medical Press, 2020)
Kjell Gunnar Gundersen,1 Richard Potvin2 1iFocus Øyeklinikk AS, Haugesund, Norway; 2Science in Vision, Bend, OR, USACorrespondence: Kjell Gunnar GunderseniFocus Øyeklinikk AS, Sørhauggata 111, Haugesund 5527, NorwayTel +47 52808902Email kg@ifocus.noPurpose: To compare uncorrected and best-corrected visual acuity, low contrast acuity, residual refraction and ocular biometry after low cylinder power toric intraocular lens (IOL) or non-toric IOL implantation.Patients and Methods: This was a non-interventional comparative study of visual outcomes after uncomplicated cataract or refractive lens exchange surgery with either a low cylinder (Low_Cyl) or non-toric (Non_Toric) IOL of similar design implanted (AcrySof® T2 IQ Toric IOL and AcrySof® IQ IOL). Subjects in both groups had to have been eligible for the low cylinder IOL based on biometry. They had to have uncorrected distance visual acuity (UDVA) of 20/32 (0.2 logMAR) or better at the time of their single diagnostic study visit. Clinical evaluation included the manifest refraction, visual acuity (VA), low contrast VA and ocular biometry.Results: A total of 94 eyes were enrolled, 51 Low_Cyl and 43 Non_Toric. The mean manifest refractive cylinder was statistically significantly lower (∼ 0.25 D) in the Low_Toric group (p < 0.01) and significantly more eyes had 0.25 D or less of refractive cylinder in that group (p = 0.03). The orientation of the preoperative anterior corneal astigmatism was a significant cofactor, with the difference between groups more evident when astigmatism was against the rule. Uncorrected high contrast visual acuity was statistically significantly better in the Low_Toric group (p = 0.02) as was the percentage of eyes with 20/20 visual acuity (p = 0.05). Uncorrected low contrast visual acuity was not statistically significantly different in mesopic or photopic conditions.Conclusion: The low cylinder power toric IOL provided better uncorrected visual acuity and lower residual refractive cylinder than a similar non-toric IOL after cataract surgery.Keywords: toric IOL, low cylinder, low contrast acuity, astigmatism correction